2016
DOI: 10.1038/srep34299
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus A16 induced neurological disorders in young gerbils which could serve as a new animal model for vaccine evaluation

Abstract: Coxsackievirus A16 (CA16) is one of the major pathogens associated with human hand, foot, and mouth disease (HFMD) in the Asia-pacific region. Although CA16 infections are generally mild, severe neurological manifestations or even death has been reported. Studies on CA16 pathogenesis and vaccine development are severely hampered because the small animal models that are currently available show major limitations. In this study, gerbils (Meriones unguiculatus) were investigated for their suitability as an animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…This is one of the biggest advantages of our model because it is clear that virus adaptation introduces a considerable number of nucleotide variations in viral genome that may dramatically alter the course of natural infection [35, 69]. Despite the variety of geographical sources for EV-D68, the strains detected in recent years have similar VP1 sequences as long as they belong to the same genetic clade [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the biggest advantages of our model because it is clear that virus adaptation introduces a considerable number of nucleotide variations in viral genome that may dramatically alter the course of natural infection [35, 69]. Despite the variety of geographical sources for EV-D68, the strains detected in recent years have similar VP1 sequences as long as they belong to the same genetic clade [33].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al. (). It was found that immune cells from Acomys , gerbils and xid mice, but not from Mus controls, failed to respond to specific thymus‐independent type 2 (TI‐2) antigens and that Acomys , gerbils and xid mice lack a subset of B lymphocytes present in normal mice (Pennello et al., ).…”
Section: Inflammation and Immunity In Regeneration Within Mammalian Smentioning
confidence: 99%
“…The regeneration capacity of gerbils appears untested, but immune deficiencies rendering these rodents much more susceptible than mice or rats to various viral, bacterial, and parasitic infections make them an important model of many human diseases, e.g. Sun et al (2016). It was found that immune cells from Acomys, gerbils and xid mice, but not from…”
Section: Mus Acomysmentioning
confidence: 99%
“…HFMD courses are usually mild or self-limited, but a few patients could have severe symptoms or even die. In recent years, there have been several outbreaks in the West Pacific region, such as in China, Japan, Thailand, and so on [1][2][3]. There are also many HFMD case reports in Europe, such as in France and Denmark [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The gerbil has been a suitable animal model for medical use for more than 40 years, especially for cerebral infarction. Our team established a gerbil animal model for infection with both the EV71 and CVA16 viruses successfully [2,3]. The gerbil model is more sensitive to the EV71 and CVA16 viruses than the mouse model.…”
Section: Introductionmentioning
confidence: 99%